2.8 Synthetic Approaches to Fluorinated α-Amino Acids - Lloyd,C. M.; Dowell,K. F.; Brittain,W. D. G. (Modern Strategies in Organofluorine Chemistry 2, 2026)
Fluorine incorporation into peptides and biomolecules is an area that has seen rapid growth over the last few decades. The installation of fluorine atoms into peptides can improve their stability, potency, and membrane permeability, offering substantial benefits in pharmaceutical applications. Being able to introduce fluorine into these classes of molecules often relies on the ability to access the prerequisite fluorinated amino acid building blocks. This review will summarize the advancements made by synthetic chemists to access proteinogenic fluorinated α-amino acids including biosynthetic, electrochemical, and enantioselective approaches.
Keywords: Referencework; fluorine; organofluorine chemistry; amino acids; peptide synthesis; fluorination; asymmetric synthesis; trifluoromethylation; electrochemistry; biosynthesis